New Issues in Intellectual Property Law in Indonesia - M. Hawin (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2011)
This article compares the provisions on moral rights in Indonesian Copyright Act, Copyright Bill, and The Berne Convention. The legality of parallel importation and the sui generis protection of traditional knowledge are also observed by referring to the Copyright Bill and Traditional Knowledge Bill. Tulisan ini membandingkan pengaturan mengenai hak moral menurut Undangundang Hak Cipta, RUU Hak Cipta dan Konvensi Berne. Selain itu, tulisan ini juga mengkaji legalitas impor paralel dan perlindungan sui generis terhadap pengetahuan tradisional dengan merujuk kepada RUU Hak Cipta dan RUU Pengetahuan Tradisional.